d4eb17477d194b1a276a69b5cb4269441006564e
[~helmut/bidiragda.git] / FreeTheorems.agda
1 module FreeTheorems where
2
3 open import Level using () renaming (zero to ℓ₀)
4 open import Data.Nat using (ℕ)
5 open import Data.List using (List ; map)
6 open import Data.Vec using (Vec) renaming (map to mapV)
7 open import Function using (_∘_)
8 open import Function.Equality using (_⟶_ ; _⟨$⟩_)
9 open import Function.Injection using (module Injection) renaming (Injection to _↪_)
10 open import Relation.Binary.PropositionalEquality using (_≗_ ; cong) renaming (setoid to EqSetoid)
11 open import Relation.Binary using (Setoid)
12 open Injection using (to)
13
14 import GetTypes
15
16 module ListList where
17   get-type : Set₁
18   get-type = {A : Set} → List A → List A
19
20   open GetTypes.ListList public
21
22   postulate
23     free-theorem : (get : get-type) → {α β : Set} → (f : α → β) → get ∘ map f ≗ map f ∘ get
24
25   assume-get : get-type → Get
26   assume-get get = record { get = get; free-theorem = free-theorem get }
27
28 module VecVec where
29   get-type : (ℕ → ℕ) → Set₁
30   get-type getlen = {A : Set} {n : ℕ} → Vec A n → Vec A (getlen n)
31
32   open GetTypes.VecVec public
33
34   postulate
35     free-theorem : {getlen : ℕ → ℕ} → (get : get-type getlen) → {α β : Set} → (f : α → β) → {n : ℕ} → get {_} {n} ∘ mapV f ≗ mapV f ∘ get
36
37   assume-get : {getlen : ℕ → ℕ} → (get : get-type getlen) → Get
38   assume-get {getlen} get = record { getlen = getlen; get = get; free-theorem = free-theorem get }
39
40 module PartialVecVec where
41   get-type : {I : Setoid ℓ₀ ℓ₀} → (I ↪ (EqSetoid ℕ)) → (I ⟶ (EqSetoid ℕ)) → Set₁
42   get-type {I} gl₁ gl₂ = {A : Set} {i : Setoid.Carrier I} → Vec A (to gl₁ ⟨$⟩ i) → Vec A (gl₂ ⟨$⟩ i)
43
44   open GetTypes.PartialVecVec public
45
46   postulate
47     free-theorem : {I : Setoid ℓ₀ ℓ₀} → (gl₁ : I ↪ (EqSetoid ℕ)) → (gl₂ : I ⟶ (EqSetoid ℕ)) (get : get-type gl₁ gl₂)  → {α β : Set} → (f : α → β) → {i : Setoid.Carrier I} → get {_} {i} ∘ mapV f ≗ mapV f ∘ get
48
49   assume-get : {I : Setoid ℓ₀ ℓ₀} → (gl₁ : I ↪ (EqSetoid ℕ)) → (gl₂ : I ⟶ (EqSetoid ℕ)) (get : get-type gl₁ gl₂) → Get
50   assume-get {I} gl₁ gl₂ get = record { I = I; gl₁ = gl₁; gl₂ = gl₂; get = get; free-theorem = free-theorem gl₁ gl₂ get }